Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.est.8b01011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Sources and Mixing State of Atmospheric Particles in a Metropolitan Area

Abstract: Characterizing intracity variations of atmospheric particulate matter has mostly relied on fixed-site monitoring and quantifying variability in terms of different bulk aerosol species. In this study, we performed ground-based mobile measurements using a single-particle mass spectrometer to study spatial patterns of source-specific particles and the evolution of particle mixing state in 21 areas in the metropolitan area of Pittsburgh, PA. We selected sampling areas based on traffic density and restaurant densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…A variety of experimental techniques have been used to estimate per-particle mass fractions for this purpose. They range from mass spectrometry with an aerosol time-of-flight mass spectrometer (ATOFMS; Healy et al, 2014) or a soot particle aerosol mass spectrometer (SP-AMS; Ye et al, 2018) to STXM/near edge X-ray absorption fine structure (NEXAFS) and SEM/EDX (Fraund et al, 2017;O'Brien et al, 2015).…”
Section: Measurements and Models Of The Diversity Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of experimental techniques have been used to estimate per-particle mass fractions for this purpose. They range from mass spectrometry with an aerosol time-of-flight mass spectrometer (ATOFMS; Healy et al, 2014) or a soot particle aerosol mass spectrometer (SP-AMS; Ye et al, 2018) to STXM/near edge X-ray absorption fine structure (NEXAFS) and SEM/EDX (Fraund et al, 2017;O'Brien et al, 2015).…”
Section: Measurements and Models Of The Diversity Metricmentioning
confidence: 99%
“…Note that the definition of "species" for calculating the mass fractions depends on the application. It can refer to operationally defined chemical species (Healy et al, 2014;O'Brien et al, 2015;Riemer & West, 2013;Ye et al, 2018), or it can be based on elemental composition (Fraund et al, 2017;O'Brien et al, 2015). Table 8 lists the species definition used the individual field studies that reported the mixing state parameter.…”
Section: Measurements and Models Of The Diversity Metricmentioning
confidence: 99%
“…Downtown also has a higher road length density compared to West Oakland and port and, as a result, can accommodate a larger traffic volume per km 2 . Further, poor ventilation of vehicle emissions in downtown can also contribute to higher HOA levels (Yuan et al, 2014). During midday and afternoon, however, port has similar or higher HOA than downtown.…”
Section: Hoamentioning
confidence: 99%
“…11,[13][14][15] A parameterization approach has been developed to provide a quantitative description of particle diversity and mixing state. [16][17][18][19] This approach requires chemical characterization of atmospheric particles on the single particle level as a model input. However, quantification and characterization of tiny amounts of chemicals in submicron single particle is an analytical challenge.…”
Section: Introductionmentioning
confidence: 99%
“…18,[20][21][22] Realtime single particle mass spectrometry is another advanced analytical approach that has been utilized to measure chemical composition of individual particles in urban environments [23][24][25] and to identify the influence of different anthropogenic emissions and atmospheric processing on the particle diversity and mixing state. 17,19 Ye et al 19 recently investigated the evolution of mixing state of primary and secondary aerosol across the urban scale using single particle mass spectroscopy on a mobile platform. They reported that the particle mixing state in the city center showed large spatial heterogeneity that is mostly driven by local emissions, whereas particles were more internally mixed in the upwind and downwind of the urban areas.…”
Section: Introductionmentioning
confidence: 99%